Do u smoke after txt? Results of a randomised trial of smoking cessation using mobile phone text messaging. Issue 4 (26th July 2005) - Rodgers, A; Corbett, T; Bramley, D; Riddell, T; Wills, M; Lin, R-B; Jones, M
Abstract : Objectives: To determine the effectiveness of a mobile phone text messaging smoking cessation programme. Design: Randomised controlled trial Setting: New Zealand Participants: 1705 smokers from throughout New Zealand who wanted to quit, were aged over 15 years, and owned a mobile phone were randomised to an intervention group that received regular, personalised text messages providing smoking cessation advice, support, and distraction, or to a control group. All participants received a free month of text messaging; starting for the intervention group on their quit day to assist with quitting, and starting for the control group at six months to encourage follow up. Follow up data were available for 1624 (95%) at six weeks and 1265 (74%) at six months. Main outcome measures: The main trial outcome was current non-smoking (that is, not smoking in the past week) six weeks after randomisation. Secondary outcomes included current non-smoking at 12 and 26 weeks. Results: More participants had quit at six weeks in the intervention compared to the control group: 239 (28%) v 109 (13%), relative risk 2.20 (95% confidence interval 1.79 to 2.70), p < 0.0001. This treatment effect was consistent across subgroups defined by age, sex, income level, or geographic location (p homogeneity > 0.2). The relative risk estimates were similar in sensitivity analyses adjusting for missing data and salivary cotinine verification tests. Reported quit rates remained high at six months, but there was some uncertainty about between group differences because of incomplete follow up. Conclusions: This programme offers potential for a new way to help young smokers to quit, being affordable, personalised, age appropriate, and not location dependent. Future research should test these findings in different settings, and provide further assessment of long term quit rates.